Design and theoretical analysis of dynamic indentation experimental device. (December 2020) - Xiaoyan, Niu; Shenzhen, Li; Xuchen, Geng; Cong, Chen; Jiang, Zhou
Abstract: Under the conditions of vibration, drop and impact loadings, the effect of strain rate on the mechanical properties of materials is crucial. Considering the limitations of traditional test methods in testing dynamic mechanical properties of materials at micron level, a set of dynamic indentation experiment system is established based on the Split Hopkinson Pressure Bar technology and the principle of nanoindentation testing. For the first time, a mechanical calculation model for dynamic indentation experiment is proposed, and the load-displacement relationship of materials is deduced by combining with one-dimensional stress wave theory. Then the calculated load-displacement relationship of materials is given by combining the displacement derived from the one-dimensional stress wave theory with the load calculated by the mechanical calculation model. Compared with the load-displacement relationship obtained from the FE model, the two are in good agreement, which verifies the validity of the theoretical derivation.